1969
DOI: 10.1136/gut.10.12.963
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria, bile and the small bowel

Abstract: SUMMARY Microbial populations of the small bowel and bile salt metabolism were studied in 15 patients with lesions of the stomach and small intestine. These types of microorganism could be correlated with the site and extent of stasis in the small bowel and the presence of a normally functioning stomach. The presence of obligate anaerobes (bacteroides) and free bile acids could be correlated with areas of stagnation. When these abnormalities were detected throughout the small bowel, steatorrhoea was also noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(50 citation statements)
references
References 23 publications
2
47
0
1
Order By: Relevance
“…Fuchs et al (1976) also observed that the fecal anaerobes increased significantly after a fiber-rich diet accompanied by an increased fecal weight. The changes in such fecal flora seem to accelerate bile acid deconjugation resulting in an increase in bile acid excretion into the feces and therefore bile acid turnover (Gorbach and Tabaqchali 1969;Neale et al 1972). Under these conditions the fecal fat excretion is known to increase (Neale et al 1972), as shown in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Fuchs et al (1976) also observed that the fecal anaerobes increased significantly after a fiber-rich diet accompanied by an increased fecal weight. The changes in such fecal flora seem to accelerate bile acid deconjugation resulting in an increase in bile acid excretion into the feces and therefore bile acid turnover (Gorbach and Tabaqchali 1969;Neale et al 1972). Under these conditions the fecal fat excretion is known to increase (Neale et al 1972), as shown in this study.…”
Section: Discussionmentioning
confidence: 51%
“…This seems to be the only reported case where other causes of malabsorption have been excluded. There seems little doubt that bacterial overgrowth may occur in the presence of solitary duodenal diverticula (Gorbach and Tabaqchali, 1969;Tabaqchali and Booth, 1970;Tabaqchali, Hatzioannou and Booth, 1968) and that steatorrhoea and nutritional deficiency may occur in the presence of duodenal diverticula (Brey et al, 1971;Clark, 1971;Gillespy, 1957;Goldstein et al, 1963). That the malabsorption and the diverticula are causally related, however, seems seldom to have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, an attempt is made to correlate the gastrointestinal disturbance in patients with hypogammaglobulin-Received for publication 28 November 1971. aemia with the number of bacteria in the jejunum and with possible abnormalities of bile salt metabolism. Deconjugation of bile salts can be the cause of steatorrhoea in patients without immunological deficiency (Gorbach and Tabaqchali, 1969).…”
mentioning
confidence: 99%